2022
DOI: 10.1186/s12889-021-12362-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and perceptions of COVID-19 vaccine and refusal to receive COVID-19 vaccine among healthcare workers in northeastern Ethiopia

Abstract: Background Major efforts are being made to control the spread and impacts of the coronavirus pandemic using vaccines. Ethiopia began on March 13, 2021, to vaccinate healthcare workers (HCWs) for COVID-19 with the AstraZeneca vaccine. However, willingness to be vaccinated depends to a large extent on factors beyond the availability of vaccines. This study aimed to determine the rate of intention to refuse COVID-19 vaccination   and associated factors among HCWs in northeastern Ethiopia. northeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
85
9
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(143 citation statements)
references
References 19 publications
12
85
9
3
Order By: Relevance
“…Consistent with the findings of an earlier study [ 24 ], our results revealed that stronger perceptions about the effectiveness of a COVID-19 vaccine for children significantly reduced parental vaccination refusal. Perceptions about COVID-19 vaccine effectiveness have also been associated with parents’ acceptance of vaccination against COVID-19 for their children in previous studies [ 10 , 11 ] and with COVID-19 vaccination acceptance in other population groups, including adults [ 41 , 42 , 43 ], university students [ 44 ], and healthcare workers [ 45 ]. This is also one of the barriers to COVID-19 vaccine acceptance in general populations and other subgroups [ 42 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Consistent with the findings of an earlier study [ 24 ], our results revealed that stronger perceptions about the effectiveness of a COVID-19 vaccine for children significantly reduced parental vaccination refusal. Perceptions about COVID-19 vaccine effectiveness have also been associated with parents’ acceptance of vaccination against COVID-19 for their children in previous studies [ 10 , 11 ] and with COVID-19 vaccination acceptance in other population groups, including adults [ 41 , 42 , 43 ], university students [ 44 ], and healthcare workers [ 45 ]. This is also one of the barriers to COVID-19 vaccine acceptance in general populations and other subgroups [ 42 ].…”
Section: Discussionmentioning
confidence: 95%
“…The perceived safety of COVID-19 vaccines affected parents’ decisions about vaccinating their children in the current study, which was consistent with what has been reported in Korean [ 38 ], and Jordanian populations [ 24 ]. Earlier studies found that hesitancy was largely due to safety concerns [ 36 , 45 ]. Although the majority of the parents who participated in a Brazilian study were willing to accept COVID-19 immunization for their children, more than half were concerned about serious side effects of COVID-19 vaccines and one third were concerned about their safety [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“… 16 Refusal to be vaccinated was largely due to negative impressions of the upcoming COVID-19 vaccine. 13 , 48 As strength, the study was conducted in rural areas of low resource settings where lack of adequate health service and the predictors of willingness to receive vaccines were identified. As a limitation, social desirability bias in which residents answered questions in a manner that would be viewed favorably by others may have resulted in over-reporting of good perception as well as intended to receive the vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Even among some participants who demonstrated knowledge of this information, a high degree of concern related to their risk of TTS was still expressed, which may reflect an overestimation of a low-probability outcome in risk perception [ 34 ]. Moreover, although several studies have found a correlation between increased knowledge of COVID-19 with increased vaccine acceptability [ 37 , 38 ], one study in 605 Bangladeshi adults found that although greater COVID-19 vaccine knowledge was associated with overall vaccine intention, it was not significantly correlated with immediate vaccine uptake in the case of the COVID-19 vaccination [ 35 ]. The perceived severity of TTS also played an important role in individual risk perception.…”
Section: Discussionmentioning
confidence: 99%